Cross-cultural adaptation and validation of the Chinese version of the Perceived Emotional Expression Scale for adolescents - Duan, Jianing; Lin, Youbei; Li, Chuang; Zhao, Wangxiao; Wang, Xiuli (Frontiers in Psychiatry, 2025)
BackgroundExpressed emotion, as a crucial indicator of the family environment, has been proven to be a highly accurate psychosocial predictor of psychiatric relapse. At present, there is no standardized assessment tool to evaluate family-expressed emotions from the perspective of adolescents. This study aims to introduce the PEES-GAP scale into Chinese and assess its reliability and validity among general adolescent populations in China.MethodsThis study first used a modified Brislin model to translate the PEES-GAP scale into Chinese. Subsequently, six experts in related fields were invited to assess the Item-level content validity index (I-CVI) of the translated scale. Using convenience sampling, 827 adolescents meeting the inclusion criteria were recruited from two secondary schools and two universities in Shandong Province and Liaoning Province, China. The reliability of the scale was assessed through internal consistency, split-half reliability, and test-retest reliability. To examine the construct validity of the Chinese version of the PEES-GAP, exploratory factor analysis (EFA) was first conducted, followed by confirmatory factor analysis (CFA) to further assess its construct validity.ResultsBased on retaining the original 19 items of the scale, the final C-PEES-GAP demonstrated excellent psychometric properties, with a Cronbach’s alpha coefficient of 0.928. The I-CVI for each subscale ranged from 0.830 to 1.000, with split-half reliability of 0.855 and test-retest reliability of 0.964. The three-factor exploratory factor model explained 59.295% of the total variance, indicating a robust factor structure. The fit indices obtained from CFA included: CMIN/DF = 2.791, RMSEA = 0.077, AGFI = 0.832, TLI = 0.924, IFI = 0.935, CFI = 0.934, GFI = 0.869, and PGFI = 0.677.ConclusionFollowing rigorous translation and validation procedures, the PEES-GAP has been adapted for use in China, demonstrating robust psychometric properties. It has emerged as a valid tool for assessing perceived family emotional expression among the general adolescent population in China. Furthermore, this scale may also serve as a crucial instrument for researchers in the fields of psychology and mental health to conduct relevant research, as well as for clinical professionals to develop targeted intervention strategies addressing adolescents’ emotional issues.